Penerapan Relaksasi Otot Progresif terhadap Ketidakstabilan Kadar Gula Darah pada Pasien Hiperglikemia di Bangsal Musdalifah RS UAD - Schatzi Fiore Salsabilla; Sriyati Sriyati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Background: Diabetes mellitus is a chronic disease characterized by blood glucose levels that exceed normal values; hyperglycemia can cause damage to various organ systems that are life-threatening. Objective: This study is to apply progressive muscle relaxation to the instability of blood sugar levels in hyperglycemic patients. Method: The method used is a qualitative approach with a descriptive case study design through assessment, diagnosis, planning, implementation, and evaluation of nursing care using observation and documentation. Results: The application of progressive muscle relaxation resulted in relaxation of body organs with insufficient oxygen supply to the blood, and the patient reported feeling more relaxed and no longer feeling weak in the body organs. Conclusion: Based on the assessment conducted on Mrs. A, the results showed that Mrs. A felt easily thirsty and frequently urinated, appeared lethargic and pale, vital signs: BP 137/75 mmHg, HR 88x/min, T 36°C, SpO2 99%, and RBS 285 mg/dL.